Need Assessment of Psychologically Hurt Young spinal Injured Patients in National Institute of Traumatology and Orthopaedic Rehabilitation - Ahmed, Sk Abbas Uddin; Alam, AbuSaleh Mohammed Monirul; Kairy, RR (Bangladesh Medical Journal, 2009)
Dhaka the capital of Bangladesh is very densely populated. As unemployment increase with every moment, factory owners attract young group to job. So, without training and ability many workers embrace accident, even in crowd situation due to RTA and fall from tree and buildings thus some suffer from spinal injury with or without paraplegia. This paraplegic group of patients are not provided with psychiatric treatment during normal physical treatment due to our unawareness and suffer psychological distress which delay normal usual recovery. Objectives were to explore depth of psychological injury to plan treatment, reassurance and rehabilitation; assess the prevalence of anxiety and depression and change psychological adjustment after initial rehabilitation. This Study was done to find out psychological distress and also to highlight the need of psychological management. The study design was randomized prospective. Data gathered by questionnaire (face to face, telephone and by mail) and in-depth interview. The study was conducted from January to December 2004 at paraplegic ward of Tertiary referral Orthopaedic Institute (NITOR), Dhaka. DOI: 10.3329/bmj.v36i2.3609 Bangladesh Medical Journal 36(2) 2007 39-41